PSO-based adaptive sliding mode control of a bidirectional DC-DC converter with an improved reaching law - Cham, Julius Derghe; Koffi, Francis Lénine Djanna; Gabriel, Ekemb; Boum, Alexandre Teplaira (Institute of Advanced Engineering and Science, 2025)
This paper explores the development of an adaptive sliding mode control (ASMC) that incorporates an improved optimal reaching law. We intend to use the proposed ASMC in DC microgrids or electric vehicle applications to regulate a bidirectional (two-way) buck-mode DC-DC converter. To initiate the design process, we develop a mathematical model of the converter operating in the charging mode. A particle swarm optimization is employed to help get the controller’s gains to better performance. By capitalizing on the benefits of an ASMC algorithm, the developed controller achieves improved reaching conditions, increased robustness, and strengthened stability. The efficacy of the suggested controller in comparison to conventional sliding mode control (CSMC) and ASMC is demonstrated through MATLAB/Simulink simulations conducted on the converter. The comparison demonstrates that the proposed controller achieves the intended transient response in steady-state conditions with minimal error and better reference tracking. The performance of the suggested controller is robust with regard to the rejection of variations in source voltage and load resistance. For applications involving DC microgrids or electric vehicles, the suggested controller will guarantee a consistent DC transit voltage.